THE INFLUENCE OF SERVICE QUALITY, LOCATION, PRICE AFFORDABILITY, AND TRUST ON CUSTOMER SATISFACTION AT DADI LAUNDRY - Ayuningtiyas, Dita; Ismail, Harries Arizonia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of Service Quality, Location, Price Affordability, and Trust on Customer Satisfaction in Dadi Laundry's service. The research method used is quantitative with a survey approach by distributing questionnaires to 100 customer respondents. The data analysis technique employed multiple linear regression using SPSS software. The results show that simultaneously, all four independent variables have a significant effect on customer satisfaction. Partially, Service Quality and Location have a negative and significant effect, indicating that services and location not aligned with customer expectations can reduce satisfaction. On the other hand, Price Affordability and Trust have a positive and significant influence. Trust is the most dominant variable, indicating that customers' sense of security and confidence in the laundry service plays a major role in forming satisfaction. These findings highlight the importance of maintaining competitive pricing and building customer trust to increase satisfaction and loyalty in the laundry service sector.